Changes in arterial stiffness measures during mid pregnancy in women with a history of chronic hypertension. (18th April 2012) - Cockerill, R; Chmiel, C; Crocker, I; Myers, J
Abstract : Introduction: Chronic hypertension complicates between 1 – 2% of pregnancies; of these 20 – 25% develop complications including pre-eclampsia and/or fetal growth restriction. Outside of pregnancy measures of arterial stiffness have been shown to be beneficial in antihypertensive intervention trials. The Tensioclinic™ arteriograph can be used to obtain haemodynamic measurements using a brachial artery cuff. This study aimed to assess changes in arterial stiffness over mid gestation as a measure of vascular adaptation to pregnancy in women with chronic hypertension. Methods: Women attending a specialist antenatal clinic for women with chronic hypertension were invited to take part in the study. Longitudinal haemodynamic measurements (peripheral blood pressure, augmentation index (Aix %) and pulse wave velocity (PWV m/s) were obtained in left lateral using the Tensioclinic™ Arteriograph between 10-30 weeks. Uterine artery Doppler indices were also recorded. Results: To date, measurements have been obtained from 9 women. Longitudinal measurements of Aix and PWV identified 5 women with a decrease in arterial stiffness between the first and late second trimester; the same women did not have a significant reduction in peripheral blood pressure. Haemodynamic measurements (MAP, Aix, PWV) were not significantly correlated to uterine artery indices (n=27; p>0.05). Conclusion: Arterial stiffness measures are more closely correlated to peripheral vascular tone than blood pressure alone and may be more informative than BP alone in the assessment of vascular function in pregnancy. Identification of women with chronic hypertension with a failed vascular adaptation to pregnancy may be important in the prediction of later pregnancy complications.